PEMBERDAYAAN KEMAMPUAN BERWIRAUSAHA KELOMPOK PENGANGGURAN PERKOTAAN - Syamsi, Ibnu (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2018)
The purpose of this study was to make a device of the development of an entrepreneurship training, develop a model of the entrepreneurship training, and create the material of entrepreneurship training for the employment of jobless townspeople. The study employed research and development as the method and used qualitative and quantitative approaches as the methods of analyses. After a series of try-outswere conducted, the real field operational test was performed by using a pre-test and post-test design. The data were collected through interviews, participative observations, intensive discussion, documentation study, and questionnaires. A mark-test was utilized for the descriptiveand inferential statistical calculations. Findings of the study consisted of a design of the entrepreneurship training device for the applicant of the fresh entrepreneur group in the city, a model of entrepreneurship training for the employment of jobless townspeople, an entrepreneurship training material modulefor the employment of joblesstownspeople, and an effective model of entrepreneurship training and material for the employment of jobless townspeople.